2006
DOI: 10.1111/j.1552-6909.2006.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Infant Temperatures With Twins During Shared Kangaroo Care

Abstract: In a case study, two sets of premature twins were held in Shared Kangaroo Care (KC) while maternal breast and infant body temperatures were recorded. Infant temperatures remained warm and increased during KC and each breast appeared to respond to the thermal needs of the infant on that breast. Physiologic explanations for thermal synchrony exist. The data suggests that twins can be simultaneously held in KC without physiologic compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
(40 reference statements)
1
26
0
1
Order By: Relevance
“…Thorax plumage temperature was warmer in females than in males, but was not influenced by the clutch size enlargement or an interaction between sex and clutch enlargement. Hoe et al, 1992;Ludington-Hoe et al, 2006). These findings, in combination with our own, point to interesting differences between male and female parents in the modulation of offspring temperature, and suggest that such differences may be more widespread in endotherms than is currently recognized.…”
Section: Research Articlesupporting
confidence: 64%
“…Thorax plumage temperature was warmer in females than in males, but was not influenced by the clutch size enlargement or an interaction between sex and clutch enlargement. Hoe et al, 1992;Ludington-Hoe et al, 2006). These findings, in combination with our own, point to interesting differences between male and female parents in the modulation of offspring temperature, and suggest that such differences may be more widespread in endotherms than is currently recognized.…”
Section: Research Articlesupporting
confidence: 64%
“…Several comparative studies have been commissioned to establish effectiveness between KMC and conventional methods of care in both developed and developing countries, with most concluding that KMC offers additional advantages, regarding mother's empowerment and family bonding to the preterm babies [5] Physiologically, mother's breasts respond to baby's thermal needs. Mother's temperature rises when the baby's temperature is low [6]. In addition, other studies have indicated significant positive findings in weight gain, high survival rates, early initiation of breastfeeding, strong maternal-infant attachment, shorter hospital stay, and reduced parental stress in KMC as compared to conventional forms of care [7][8][9].…”
Section: Introductionmentioning
confidence: 91%
“…Literature [6] suggests that skin-to-skin contact during KMC enables a mother's breasts to generate heat in response to the thermal needs of the baby.…”
Section: Discussionmentioning
confidence: 99%
“…As a result the lungs will function better (Bergman 2014). In a powerful case report published by Ludington-Hoe et al(2006), a mother's skin was able to respond to two babies different thermal needs at the same time, suggesting twins can also be simultaneously held in KMC without physiologic compromise.…”
Section: Review Of Systemsmentioning
confidence: 99%